Analysis Of The Determinants Of International Migration Of Indonesian Migrant Workers From City Districts In Bali Province - Ni Luh Wiwik Candrika Sari; Ni Made Tisnawati (International Journal of Management Research and Economics, 2024)
Bali Province is the seventh province in Indonesia where many people migrate internationally. The existence of economic problems in Bali Province such as unemployment and poverty that continue to increase every year causes many residents to choose to become migrant workers. In addition, although the level of education possessed by residents in Bali Province is fairly capable, they prefer to become migrant workers to be able to get the opportunity to get higher wages abroad. This study aims to analyze the simultaneous and partial influence of the variables of education level, poverty level, district minimum wage, and unemployment rate on the level of international migration of PMI from city districts in Bali Province during 2014-2023 in 90 observations. The research method in this study is a quantitative research method using panel data analysis techniques and moderation analysis. The results obtained from this study: 1) Simultaneously, education level, poverty level, district minimum wage, and unemployment rate affect the international migration rate of migrant workers. 2) Partially, education level and poverty level have a positive and significant effect on the international migration rate of migrant workers while the district minimum wage and unemployment rate have a negative and significant effect on the international migration rate of migrant workers. 3) The unemployment rate variable is a pseudo-moderating variable. The unemployment rate variable is a variable that strengthens the influence of education level and poverty level on the international migration rate of migrant workers while the unemployment rate variable is a variable that weakens the influence of the district minimum wage on the international migration rate of migrant workers from city districts in Bali Province.